1995
DOI: 10.1172/jci117822
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate decarboxylase-, insulin-, and islet cell-antibodies and HLA typing to detect diabetes in a general population-based study of Swedish children.

Abstract: Most autoimmune diabetes occurs in those without a diabetic relative, but few cases are identifiable prospectively. To model general population prediction, 491 consecutive newly diabetic children from all of Sweden were tested for autoantibodies to glutamate decarboxylase (GAD65ab), insulin (IAA), and islet cells (ICA), and for HLA-DQ genotypes by PCR; 415 matched control children were tested in parallel. GAD65ab sensitivity/specificity was 70/96%, versus 84/96% for ICA, 56/97% for IAA, 93/93% (any positive), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
141
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 32 publications
22
141
1
3
Order By: Relevance
“…It has been reported that patients with young age at onset of diabetes (≤25 year) have increased frequencies of HLA-DQB1 *02/0302 genotypes [27-30], however; according to our study significant associations between HLA-DQB1 genotypes and young age at onset was due to islet antibodies. In agreement with previous observations [31][32][33], GADA were associated with HLA-DQB1 *02/*0302, whereas IA-2A were associated with HLA-DQB1 *0302/X and *0302/*0604, respectively. Indeed, IA-2A concentration was highest among patients with the HLA-DQB1 *0302/X genotype.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that patients with young age at onset of diabetes (≤25 year) have increased frequencies of HLA-DQB1 *02/0302 genotypes [27-30], however; according to our study significant associations between HLA-DQB1 genotypes and young age at onset was due to islet antibodies. In agreement with previous observations [31][32][33], GADA were associated with HLA-DQB1 *02/*0302, whereas IA-2A were associated with HLA-DQB1 *0302/X and *0302/*0604, respectively. Indeed, IA-2A concentration was highest among patients with the HLA-DQB1 *0302/X genotype.…”
Section: Discussionsupporting
confidence: 93%
“…Because autoantibodies are biological markers for preclinical diabetes, it is important to know whether these autoantibodies show evidence for genetic determination, or whether they merely reflect the presence of non-genetic diabetes-predisposing factors (such as viruses that damage beta cells). In the general population, the frequencies of ICA, IAA, and anti-GAD are low ± for example, 3±4 % in a study of Swedish children [31] and 2 % in a study of British children [28]. The frequencies among siblings of Type I diabetics are somewhat higher ± for example, 6 % of siblings were ICA + in one large study [32].…”
Section: Evidence For a Genetic Basis: Family And Twin Studies Of Typmentioning
confidence: 97%
“…This raises the question of whether autoantibody positivity, used as a marker for screening, confers the same risk for individuals from the general population as it does for individuals who have a family member with type 1 diabetes and therefore share other genetic factors (primarily HLA) that may be important in the disease process. Although population screening approaches have varied, it is clear that higher levels of autoantibodies as well as multiple autoantibody positivity confer a higher predictive value for type 1 diabetes in the general population, just as they do in first-degree relatives (15,25). The Finnish Type 1 Diabetes Prediction and Prevention (DIPP) project used a screening strategy in which genetic susceptibility of newborns is evaluated by first genotyping for HLA markers known to confer increased or decreased risk for type 1 diabetes, followed by repeated measurements for autoantibody positivity in genetically susceptible individuals (26).…”
Section: Islet Cell Autoantibodies Predict Autoimmune Diabetesmentioning
confidence: 99%